Valuasi ekonomi Danau Poso mengacu market based approach - Sibarani, Geraldy; Riskyoval, Riskyoval; Kartika, Y P (Badan Kerjasama Pusat Studi Lingkungan (BKPSL) se-Indonesia bekerjasama dengan Pusat Penelitian Lingkungan Hidup IPB (PPLH-IPB), 2022)
Lake Poso in Central Sulawesi Province holds a lot of potential, namely as a source of clean water, producing electricity, tourism and aquatic biodiversity. The increasing number of residents on the outskirts of Lake Poso, causes pollution in Lake Poso in the form of household waste and agricultural runoff. The purpose of the study was to assess the economic aspects of Lake Poso in terms of the benefits of the lake. An assessment of the Lake Poso ecosystem with a market-based approach was carried out, through the collection of market data on lake users. The data includes the price of PDAM water of Rp 2,000/m3, the price of rice was Rp 8,000/kg, and the price of eel was Rp 80,000/kg. Based on these costs, the results obtained are: First, the value of the benefits of clean water was Rp. 1,132,624,200. Second, the value of water as water for agricultural irrigation was Rp 17,040,000,000. Third, the value of benefits from the production of eel was Rp 1,600,000,000. The total value of the benefits of Lake Poso was Rp 19,772,624,200.